Gerakan Dakwah Mualaf Centre Indonesia di Kota Padang - Nur Annisa Tri Handayani; Suparto (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Mualaf Center Indonesia Peduli (MCIP) in Padang focuses on mentoring and supporting new converts, providing religious education and guidance to strengthen their faith and understanding of Islam. This organization organizes religious mentoring programs in mosques to help new converts overcome internal conflicts and adapt to their new beliefs, ensuring they do not return to their previous religion. The research methodology used in this study is qualitative descriptive (Library Research). The term convert refers to non-Muslims who have converted to Islam and need guidance to increase their faith in Allah, who often face challenges from family and relatives from their previous religion. Factors that encourage someone to convert to Islam include spiritual search, dissatisfaction with previous beliefs, marriage to a Muslim partner, and guidance from social and cultural influences. Based on the research conducted, it can be concluded that in the da'wah movement at MCIP in Padang city, namely the socialization and study guidance program, spiritual services including personal and Islamic consultations, which programs have benefits for converts in increasing religious understanding and strengthening faith.